Single and combined associations of blood lead and essential metals with serum lipid profiles in community-dwelling adults - Wan, Heng; Wang, Dongmei; Liang, Yongqian; He, Yajun; Ma, Qintao; Li, Tingting; He, Yingbo; Guo, Hanquan; Wang, Jiachen; Li, Zhao; Lin, Xu; Liu, Lan; et al. (Frontiers in Nutrition, 2023)
Background: Although several studies have examined the relationships between lead (Pb) exposure and serum lipid profiles, the associations of the metal mixture, including lead (Pb) and essential metals with lipid profiles remain unclear. Objective: To investigate the associations of the metal mixture including Pb and essential metals [magnesium (Mg), manganese (Mn), copper (Cu), iron (Fe), zinc (Zn), and calcium (Ca)] with serum lipid profiles [total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C)], as well as the potential interactions among the metals. Methods: 998 Chinese community-dwelling adults completed a questionnaire and underwent checkups of anthropometric parameters, serum lipid profile levels (TC, TG, LDL-C, and HDL-C), blood metal concentrations (Pb, Mg, Mn, Cu, Fe, Zn, and Ca). The multivariable linear regression, weighted quantile sum (WQS) regression, and Bayesian kernel machine regression (BKMR) were applied to evaluate the single and combined associations of blood Pb and essential metals with serum lipid profiles. Results: In the multivariable linear regression model, the blood Pb was positively associated with TC, LDL-C, and HDL-C (P <0.05, all), and the blood Mg were positively associated with serum TC, LDL-C, and Ln TG (P <0.05, all). In the WQS regression and BKMR models, the metal mixture of blood Pb and the essential metals was positively associated with all of the serum lipid profiles. In addition, an inverse U-shaped association of Pb with Ln TG and the positive interactive effect between blood Pb and Mg levels on TC and LDL-C were found. Conclusions: The levels of blood Pb, together with the essential metals, especially Mg levels, are suggested to be considered when assessing dyslipidemia risk. However, more evidence is still needed to validate the conclusions.